2018
DOI: 10.1103/physrevd.98.043514
|View full text |Cite
|
Sign up to set email alerts
|

Cogenesis of LIGO primordial black holes and dark matter

Abstract: In this letter, we propose a novel scenario which simultaneously explains O(10)M primordial black holes (PBHs) and dark matter in the minimally supersymmetric standard model. Gravitational waves (GWs) events detected by LIGO-Virgo collaboration suggest an existence of black holes as heavy as ∼ 30M . In our scenario, as seeds of the PBHs, we make use of the baryon number perturbations which are induced by the special type of Affleck-Dine mechanism. Furthermore, the scenario does not suffer from the stringent co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 60 publications
(81 reference statements)
2
36
0
Order By: Relevance
“…In this section, we briefly review the generation of inhomogeneous baryon asymmetry and high baryon bubbles (HBBs) based on [37,38].…”
Section: Hbbs From Affleck-dine Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we briefly review the generation of inhomogeneous baryon asymmetry and high baryon bubbles (HBBs) based on [37,38].…”
Section: Hbbs From Affleck-dine Fieldmentioning
confidence: 99%
“…(For another example, see [36].) Recently, Hasegawa and one of authors [37,38] showed that the inhomogeneous Affleck-Dine baryogenesis is realized in the framework of the minimal supersymmetric standard model (MSSM) and it produce high baryoin bubbles (HBBs) which is regions with high baryon-to-entropy ratio η b . Those HBBs collapse into PBHs with masses 10M that explain the LIGO gravitational wave events.…”
Section: Introductionmentioning
confidence: 99%
“…The axion bubble is analogous to the high baryon bubble in inhomogeneous Affleck-Dine baryogenesis [21,23,24]. The axion bubbles are formed when the transient PQ breaking turns on and the axion field is dynamically set at the nearest minimum, well before the QCD phase transition.…”
Section: Dark Mattermentioning
confidence: 99%
“…The PBH formation in the Affleck-Dine mechanism was studied in Refs. [21][22][23][24][25]. In this case, large inhomogeneity of the Affleck-Dine field is realized by the inflationary fluctuation and nontrivial post-inflationary dynamics in the presence of the multiple vacua.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation